Micro-organisms involved in iron oxidation and acid mine drainage formation in KwaZulu-Natal and their control by soil covers on coal waste dumps - Modinger, Heinrich (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 1998.